The third International Workshop on neutrino oscillations and their origin : (World Scientific, 2002)
This volume brings together international experts in diverse areas of physics to discuss recent progress in the experimental and theoretical study of neutrino oscillations. Readers are brought up to date with the latest developments in important neutrino experiments, and the associated progress in theory is summarized. The principal projects worldwide, such as Super-Kamiokande, SNO, KamLAND, are considered, and contributions also report on future experiments, including JPARC, OPERA, and MINOS. Several other related topics, such as dark matter, double beta decay, lepton flavour violation, and cosmology, are discussed, reflecting the wide-ranging specializations of many contributors outside of pure neutrino physics.